Elaboración De Planos Técnicos Del Sistema Helice- Viga Del Laboratorio De Detectores Sede - Morales Cortes, Néstor Ferney (Universidad Antonio Nariño, 2024)
-The following document is based on the visual inspection of the propeller-beam project to establish the metrology of the mechanical parts of this project, for subsequent digitization of the information, having the correct digitization in the mechanical design will be an input for the changes futures that allow expanding the configuration of the propeller-beam system. The project presented here is based on the need to find better rigidity and damping components and mitigate the impact of the beam on its structure. Keywords: digitalization, mechanical design, metrology.